Transnational Youth Activist Networks in Asia: The Evolution and Dynamics of the Milk Tea Alliance - Phattharathanasut, Tuwanont (Annali di Ca’ Foscari: Serie Orientale)
This study examines the development and dynamics of transnational youth activism in Asia, focusing on the case of the Milk Tea Alliance (MTA). It addresses two research questions: “How did it emerge?” and “How has it continued until today?”. Through interviews with 50 activists across Asia, the study argues that the MTA networks were developed and nurtured over many years, rather than being solely facilitated by digital communication technologies. The study identifies two key networks: the triangular network among Hongkonger, Taiwanese, and Thai youth activists, and the Network of Young Democratic Asians (NOYDA). While the triangular network was crucial in the early days, the NOYDA network became a key actor after the 2021 military coup in Myanmar. By using network analysis and a transnational historical approach, the study provides a more nuanced explanation of the recent wave of youth and student political activism in Asia. It also highlights the grassroots interconnectedness between East and Southeast Asia in the contemporary period.